Comparative safety of transvenous and leadless pacemakers in patients with cardiovascular diseases: A meta-analysis study - Cedric Mhasseb; Mayassa Kiwan; Marie-Elie Merhi; Nicolas Moussallem; Jana Moussalli; Maroun Abou Zeid; Sarah Abou Daher; Ghassan Nabbout; Sami Azar; Amjad Kanaan; Frederic Harb (Heliyon)
Background: Transvenous pacemakers (TVP) and leadless pacemakers (LP) are two reliable permanent modalities for the treatment of heart rhythm disorders. Several observational studies explored the safety and efficacy of the two devices. The aim of this meta-analysis study is to present a comparative analysis of the safety of leadless versus transvenous pacemakers. Methods: The study protocol was registered in PROSPERO registry (CRD42024520647). A comprehensive and systematic search was conducted across PubMed, Embase, Cochrane Library, Web of Science and ClinicalTrials.gov, spanning from inception until just before the final analysis. SPSS was used for statistical analysis. Relative risks (RR) and odds ratio (OR) were used to evaluate the outcomes with a 95 % confidence interval (CI). Results: Nineteen studies met the inclusion criteria and were analyzed, in which the overall effect estimate showed increased risk of major complications in the TVP group (LogOR = −0.27, 95 % CI: [-0.63, 0.10]) compared to the LP group. Among the nineteen studies, seven studies showed that TVP significantly increase the risk of reintervention (LogOR = −0.73, 95 % CI: [-1.15, −0.31]) and thirteen studies showed a higher risk of mortality among patients receiving TVP (Cohen's d = −0.11, 95 % CI: [-0.22, 0.01]) compared to those receiving LP. Conversely, a higher risk of pericardial effusion or tamponade and thromboembolic events was among patients receiving LP with (LogOR = 1.01, 95 % CI: [0.55, 1.46]) and (LogOR = 0.45, 95 % CI: [-0.33, 1.23]) respectively. Conclusion: This study showed that leadless pacemakers tend to be safer compared to transvenous pacemakers, with reduced risks of major complications, reintervention, generator malfunction, device or lead dislodgement, pneumothorax and hemothorax, infections rates, and mortality. However, higher odds of cardiac perforation and tamponade and thromboembolic events were observed among patients receiving LP. The lack of both randomized clinical trials and long term follow up studies limits our assessment and emphasizes the need for ongoing investigation to understand the extended complications associated with these devices amidst advancing technology.